Knowledge assessment of anti-snake venom among healthcare practitioners in northern Nigeria - Auwal A. Bala; Abubakar I. Jatau; Ismaeel Yunusa; Mustapha Mohammed; Al-Kassim H. Mohammed; Abubakar M. Isa; Abubakar S. Wada; Kabiru A. Gulma; Inuwa Bello; Sani Malami; Godpower C. Michael; Basheer AZ. Chedi (Therapeutic Advances in Infectious Disease, 2021)
Introduction: Anti-snake venom (ASV) is the standard therapy for the management of snakebite envenoming (SBE). Therefore, the knowledge of ASV among healthcare practitioners (HCPs) is essential for achieving optimal clinical outcomes in snakebite management. This study aimed to assess knowledge of ASV among the HCPs in northern Nigeria. Methods: We conducted a cross-sectional study involving eligible HCPs from different healthcare settings in northern Nigeria. The participants were recruited into the study using a combination of online (via Google Form) and face-to-face paper-based survey methods. The ASV knowledge of the respondents was measured using a validated anti-snake venom knowledge assessment tool (AKAT). Inadequate overall knowledge of ASV was defined as scores of 0–69.9%, and 70–100% were considered adequate overall knowledge scores. The predictors of ASV knowledge were determined using multiple logistic regression. Results: Three hundred and thirty-one (331) eligible HCPs were included in the study analysis (310 from online and 21 from paper-based survey). Overall, an estimated 12.7% of the participants had adequate knowledge of ASV. Adequate ASV knowledge was higher among physicians compared with other HCPs (21.7%; χ 2  = 8.1; p  = 0.04). Those without previous training on ASV (adjusted odds ratio [aOR], 0.37; 95% confidence interval [CI], 0.18–0.73; p  = 0.004) and who have not previously administered/dispensed ASV (aOR, 0.31; 95% CI, 0.15–0.63; p  < 0.001) were less likely to have adequate knowledge of ASV. Conclusion: The knowledge of ASV among healthcare practitioners in northern Nigeria is grossly inadequate. Experience with administering or dispensing ASV predicts ASV knowledge. Therefore, appropriate interventions are needed to improve ASV knowledge, particularly among the HCPs, for optimal healthcare outcomes.